The Influence of Parents' Socioeconomic Status on Early Childhood Language Development - Annisa Amalia Rahma; Untung Nopriansyah (Cakrawala Dini)
Parents' socioeconomic status is indirectly related to children's language development. Families with a lower socioeconomic status tend to prioritize meeting basic family needs, which may result in less attention being given to their child's language development. This study aims to investigate the impact of parents' socioeconomic status on the language development of young children. The research method used is descriptive quantitative. The data collection technique involved distributing questionnaires via Google Forms, using a Likert scale to measure the influence of parents' socioeconomic status on early childhood language development. The results of this study found that the socioeconomic status of parents has a significant impact on children's language development. Children with higher socioeconomic status parents tend to have better language development compared to children with low socioeconomic status parents. This is because children from middle-to-upper middle families tend to have better access to books, technology devices, educational toys, and additional educational that can stimulate language development. In addition, parents who have higher education are more able to provide quality language stimulation to their children. This study provides an understanding for parents as well as the community about how the socioeconomic status of parents can affect early childhood language development.